The Need for Arabic Language Teaching Materials Based on Multicultural Education for Indonesian Diaspora Students - Nuruddin Nuruddin; Budiaman Budiaman; Andri Ilham; Ahmad Muzayin Haqi (Jurnal Alsinatuna, 2021)
This study aims to analyze the need to develop a model of Arabic teaching materials containing the values ​​of multicultural-based character education, especially in Indonesian Foreign Schools (Sekolah Indonesia Luar Negeri) in Jeddah, Riyadh, and Makkah. In this needs analysis, the researcher describes the data obtained from the questionnaires of students and teachers who teach Arabic subjects with 39 respondents. This study indicates that Arabic teaching materials in Indonesian Foreign Schools, especially in Arab countries, need to be developed. Developing Arabic teaching materials with multicultural values ​​is very important to make learning Arabic at Indonesian Foreign Schools easier, more effective, fun, and produce Indonesian diaspora students who have a spirit of nationalism and respect plurality. The development of these teaching materials is manifested in three aspects, namely (1) related to Arabic language teaching materials based on the values ​​of national character education by learning objectives and contextual with the times; (2) aspects of application technology, namely by developing Arabic teaching materials equipped with multimedia learning media such as audio, video, animation, and others to make it easier to learn; (3) aspects of character education, namely Arabic teaching materials that contain character education values, such as religious values, nationalism, honesty, independence, cooperation, integrity, hard work, and responsibility